Burden of and Trends in urticaria from 1990 to 2021 in China: A time-trend analysis and comparison with the United States and United Kingdom based on the GBD 2021 - Wenxi Xiao; Lizhi Xiang; Caizhi Peng (PLoS ONE, 2025)
Background As the world’s largest developing country, China is facing a huge burden of urticaria. Studying the variations in urticaria management strategies between China and developed nations could offer valuable insights for policy development and enhance urticaria control efforts. Methods We used the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) to acquire a detailed comprehension of the rates and trends of urticaria incidence and prevalence, DALYs burden, and control strategies in China and compared them with those in the United States and the United Kingdom. Results In global both sexes, from 1990 to 2021, the all ages incidence of urticaria, age-standardized percent prevalence, and all ages DALYs cases increased from 84.8 (106, 95% UI: 74.5–96.2) to 117.0 (106, 95% UI: 104.1–131.0), 0.89% (95% UI: 0.79%−1.00%) to 0.90% (95% UI: 0.80%−1.02%), and 2.9 (106, 95% UI: 1.9–4.1) to 4.0 (106, 95% UI: 2.6–5.7), respectively. Meanwhile, the age-standardized incidence rate increased from 1529.2 (95% UI: 1355.9–1720.36) in 1990 to 1533.71 (95% UI:1358.4–1726.1) in 2021. The incidence counts and prevalence peaked in individuals aged 5–9 years for both males and females, and it shows a gradually decreasing trend in subsequent age groups. The number of incidences has shown a gradually increasing trend and the incidence was higher in female than male. In China, from 1990 to 2021, the all ages incidence of urticaria, age-standardized percent prevalence, and all ages DALYs cases increased from 16.06 (106, 95% UI: 13.97–18.23) to 17.30 (106, 95% UI: 15.37–19.25), 0.81% (95% UI: 0.71%−0.92%) to 0.79% (95% UI: 0.69%−0.90%), and 551.3 (103, 95% UI: 362.6–792.7) to 591.8 (103, 95% UI: 391.4–830.1), respectively. In general, over the past 30 years, urticaria has shown a slow growth trend in China. In the same period, age-standardized incidence rate (ASIR) decreased from 1342.4 (95% UI: 1176.0–1520.5) in 1990 to 1337.6 (95% UI: 1172.3–1514.7) in 2021. Conclusion Clinical data for special populations such as the elderly, children, and pregnant women need to be further expanded and strengthened in China. High quality randomized controlled trial research is still needed for keeping pace with advancements.